PENGARUH DISTRIBUSI PENGIRIMAN PAKET DENGAN MENGGUNAKAN METODE TRANSPORTASI TERHADAP EFISIENSI BIAYA (STUDI PADA PT. J&T Express DP GRT 01) - hasanah, nur_ (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2026)
This research is based on the use of distribution (transportation) costs at PT. J&T Express DP (Drop Point) GRT 01 which distributes packages to a number of different destination points so that often the use of transportation costs can swell. This phenomenon is caused by various factors, one of which is the distribution route. Based on this, the author conducted a study entitled